Disabilities sourcebook : basic consumer health information about disabilities that affect the body, mind, and senses, including birth defects, hearing and vision loss, speech disorders, learning disabilities, psychiatric disorders, degenerative diseases, and disabilities caused by injury and trauma, such as amputation, spinal cord injury, and traumatic brain injury ; along with facts about assistive technology, physical and occupational therapy, maintaining health and wellness, special education, legal, financial, education, and insurance issues, a glossary of related terms, and resources for additional help and information - Omnigraphics, Inc. (Detroit, MI : Omnigraphics, Inc., 2016)
"Provides basic consumer health information about physical, sensory, cognitive, and learning disabilities, along with facts about assistive devices, technologies, and related services to promote independence, and guidance for families on education and employment options, legal, and financial concerns. Includes index, glossary of related terms, and other resources"--
Introduction to disabilities -- Types of disabilities -- Assistive technology and treatment options that help people with disabilities -- Staying healthy with a disability -- Special education and support services for children with disabilities -- Legal, employment, and financial support for people with disabilities.
Includes bibliographical references and index.
Keywords: People with disabilities -- United States -- Handbooks, manuals, etc; People with mental disabilities -- United States -- Handbooks, manuals, etc